Inhibitory effects of Patchouli alcohol on the early lifecycle stages of influenza A virus - Fan, Yaohua; Zhang, Qiong; Zhang, Wen; Lai, Yanni; Long, Haishan; Huang, Huiting; Zhan, Shaofeng; Liu, Xiaohong; Lai, Jielan; Zhang, Zhongde; Pan, Pan; Su, Ziren; et al. (Frontiers in Microbiology, 2023)
The antiviral activity and underlying mechanism of Patchouli alcohol remain unclear. This study evaluated the cytotoxicity, optimal methods for drug administration, anti-influenza A activity of Patchouli alcohol. The antiviral mechanism of Patchouli alcohol was also assessed via qRT-PCR, western blot, hemagglutination inhibiting (HAI) assay, and hemolysis inhibiting assay. Patchouli alcohol was shown to have low cytotoxicity and its strongest antiviral effect was associated with premixed administration. Patchouli alcohol inhibited virus replication during the early lifecycle stages of influenza A virus infection and specifically prevented expression of the viral proteins, HA and NP. In both the HAI and hemolysis inhibiting assays, Patchouli alcohol was able to block HA2-mediated membrane fusion under low pH conditions. Patchouli alcohol had lower binding energy with HA2 than HA1. These findings suggest that Patchouli alcohol could be a promising membrane fusion inhibitor for the treatment of influenza A infection.